2016
DOI: 10.1161/jaha.115.003158
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Hospitalization for Stroke and Transient Ischemic Attack in Young Adults: A Registry‐Based Study

Abstract: BackgroundStudies have reported increasing incidence of ischemic stroke in adults younger than 50 to 55 years. Information on temporal trends of other stroke subtypes and transient ischemic attack (TIA) is sparse. The aim of this study was to investigate temporal trends of the incidence of hospitalizations for TIA and stroke including sex‐ and subtype‐specific trends in young adults aged 15 to 30 years.Methods and ResultsFrom the Danish National Patient Register, we identified all cases of first‐ever stroke an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
98
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 34 publications
7
98
1
4
Order By: Relevance
“…12 These results were corroborated at a 9,14 An increase in IS incidence was also observed in young adults in Denmark and in Sweden. 15,16 The stability of hospitalization rates for HS observed in our study is consistent with results reported in the Danish study and in the Greater Cincinnati and Northern Kentucky study. 8,15 Multiple causes could explain the increase of IS incidence in people aged <65 years.…”
Section: Changes In Hospitalized Patient Ratessupporting
confidence: 91%
See 1 more Smart Citation
“…12 These results were corroborated at a 9,14 An increase in IS incidence was also observed in young adults in Denmark and in Sweden. 15,16 The stability of hospitalization rates for HS observed in our study is consistent with results reported in the Danish study and in the Greater Cincinnati and Northern Kentucky study. 8,15 Multiple causes could explain the increase of IS incidence in people aged <65 years.…”
Section: Changes In Hospitalized Patient Ratessupporting
confidence: 91%
“…15,16 The stability of hospitalization rates for HS observed in our study is consistent with results reported in the Danish study and in the Greater Cincinnati and Northern Kentucky study. 8,15 Multiple causes could explain the increase of IS incidence in people aged <65 years. The increase in the prevalence of cardiovascular risk factors in young adults seems to be the best hypothesis in France.…”
Section: Changes In Hospitalized Patient Ratessupporting
confidence: 91%
“…23,24 While ischemic stroke historically has affected predominantly older adults, its frequency in a younger population has been increasing. 2530 This trend is of particular concern because stroke in younger individuals may lead to disability during the most productive years of life. Risk factors for ischemic stroke in young adults include hypertension, smoking, diabetes mellitus, and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for ischemic stroke in young adults include hypertension, smoking, diabetes mellitus, and obesity. 30 Stroke in young adults also has other etiologies that are not fully understood but may differ from those of ischemic stroke in individuals of more advanced age, particularly a greater association with cervical artery dissection. 31 While our study suggests mass effect and cervical dissection are associated with AIS onset after TBI, future prospective studies may help better characterize specific mechanisms leading to AIS acutely in these types of brain injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The present study focused on stroke outcomes following PAE in 3-month old young adult animals, since recent epidemiological surveys have identified a sharp increase in stroke in young adults of both sexes (Tibaek et al, 2016, Ramirez et al, 2016), caused perhaps by an increase in metabolic disease in this population. In our studies, stroke due to transient middle cerebral artery occlusion resulted in cortical and striatal infarct after 24 h of reperfusion, comparable to the types of damage observed in human populations (Kaufmann et al, 1999) and in rodent studies (Manwani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%